Systematics, toxins, parasitoids, and niche :an integrative approach to the study of a new black widow spider in Colombia (2018)
Black widow spiders have been widely studied because they are medically important due to the syndrome produced after a bite. The syndrome can produce local or systemic reactions and can be fatal. Also, because of the difficulty in their classification; the color pattern polymorphism, and the similarities in the reproductive systems have been a problem in the differentiation and taxonomic identification of species by morphology. There are 31 species of Latrodectus described worldwide, and two species described for Colombia, L. curacaviensis (Müller, 1776) and L. geometricus Koch, 1841. L. geometricus is the only cosmopolitan species and has been classified as invasive in many ecosystems; this species origin is not known yet, but the closest phylogenetic relative is from Africa. L. curacaviensis was recognized as a species after many changes in its classification. This species was last reported in Colombia in the department of Atlantico, north of the country. Black widows in Colombia are known since 1538, when Gonzalo Jimenez de Quesada reported deaths in his army by the bite of a deadly red spider in the "Valley of sadness", the Tatacoa desert, southwestern Colombia. This unknown species has been described in many natural history essays and medical articles in Colombia since that date, but they refer to the spider with the common Latin-American black widow name "coya"; there is no reference to a specific species and the knowledge of the epidemiological problem this unknown species impose, is null